2006
DOI: 10.1038/sj.leu.2404258
|View full text |Cite
|
Sign up to set email alerts
|

CUTLL1, a novel human T-cell lymphoma cell line with t(7;9) rearrangement, aberrant NOTCH1 activation and high sensitivity to γ-secretase inhibitors

Abstract: Activating mutations in NOTCH1 are present in over 50% of human T-cell lymphoblastic leukemia (T-ALL) samples and inhibition of NOTCH1 signaling with c-secretase inhibitors (GSI) has emerged as a potential therapeutic strategy for the treatment of this disease. Here, we report a new human T-cell lymphoma line CUTLL1, which expresses high levels of activated NOTCH1 and is extremely sensitive to c-secretase inhibitors treatment. CUTLL1 cells harbor a t(7;9)(q34;q34) translocation which induces the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(152 citation statements)
references
References 29 publications
8
140
0
1
Order By: Relevance
“…8,15,20,21 By flow cytometric analysis of the DNA content of propidium iodide stained cell populations, we confirmed induction of G0/G1 cell cycle arrest after 7 days of GSI treatment in all cell lines that expressed mutant NOTCH1 and displayed a GSI induced proliferation defect (data not shown).…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…8,15,20,21 By flow cytometric analysis of the DNA content of propidium iodide stained cell populations, we confirmed induction of G0/G1 cell cycle arrest after 7 days of GSI treatment in all cell lines that expressed mutant NOTCH1 and displayed a GSI induced proliferation defect (data not shown).…”
Section: Resultsmentioning
confidence: 67%
“…8,15,[19][20][21] In this study, we have further evaluated the consequences of GSI treatment of T-ALL cell lines, and investigated possible synergism between GSI and other anti-cancer agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5] Moreover, anti-NOTCH1 therapies hold the promise of providing a molecularly tailored treatment for this disease. 2,6 Early studies on the prognostic significance of NOTCH activation in T-ALL showed that NOTCH1 mutations are not associated with poor outcome and suggested that in fact they could be associated with good prognosis. Thus, an original study comprising 157 pediatric T-ALL patients from the pediatric ALL-BFM 2000 study found that NOTCH1 mutations were associated with low levels of MRD and improved relapse-free survival.…”
mentioning
confidence: 99%